Quantification of the Size of Local Public Administration: Empirical Study of Polish Regions - Skica, Tomasz; Dvouletý, Ondřej (European Spatial Research and Policy, 2018)
The issue of the size of public administration is commonly researched. Most of the times this topic is tackled from a macroeconomic perspective, considering local and central administration together. That is why this paper uniquely takes on the local perspective only, analysing the size of local government (i.e. size of public administration at the local level) in Polish regions during the period of 2009–2013. Based on the existing literature, we chose five variables of the size of local administration at the commune level connected with employment and reflecting costs related to the functioning of local administration structures. All indicators were expressed per capita. With the usage of ANOVA, we proved significant differences in the size of public administration across regions for all variables. To compare the size of local governments across regions, we ranked all variables individually, and then we calculated the average ranking for all variables. Our findings have clear implications for policy makers, providing information about the regions with the biggest/smallest size of public administration at the local level. Our study suggests simple and accessible tool for continuous reporting on the size of public administration in order to monitor costs also in the upcoming years. The results of the monitoring could also be used for the establishment of an incentive program for regional policy representatives.